Determinants of Adolescents’ Healthy Lifestyle Behavior in Kediri, East Java - Dian Jayantari Putri K Hedo; Katmini Katmini (Universitas Airlangga, 2022)
Background: Amidst the disruptive era that is full of changes and challenges during the COVID-19 pandemic, psychological strength is needed by adolescents to be able to focus on positivity and maintain optimal health functions. Adolescents are one of the high-risk groups in this world’s recent situation. Therefore, adolescents need to stay safe and healthy to survive their future, one of which is by doing healthy lifestyle behavior. In this context, resilience, self-compassion, and hope need to be considered by adolescents in order to successfully perform healthy lifestyle behavior. Objective: The research objective was to analyze the relationship between resilience, self-compassion, and hope with healthy lifestyle behavior in adolescents. Methods: This research was a descriptive-analytic study with a cross-sectional design. The population was adolescents in Kediri; East Java aged 15-19 years old. The sample was collected by cluster random sampling. The total sample of this research was 342 respondents. The independent variable was resilience, self-compassion, and hope. The dependent variable was healthy lifestyle behavior. Data were collected by offline questionnaires filled by the respondent and analyzed using regression. Results: Based on regression analysis, variables that simultaneously and significantly related to healthy lifestyle behavior were resilience, self-compassion, and hope (p<0.001). There was a significant relationship between each variable of resilience (p=0.001), self-compassion (p=0.002), and hope (p<0.001) with healthy lifestyle behavior. Conclusion: Resilience, self-compassion, and hope, both simultaneously and individually were predictors of healthy lifestyle behavior. According to the research result, adolescents need to raise awareness and practice their psychological strengths to maintain their healthy lifestyle behavior in daily life.